Implementing the Guided Pathways Model: A Case for Change Management and Transformation - Russell Frohardt; Janie C. Scott (Academic Chairpersons Conference Proceedings, 2019)
Wouldn’t we all love to roll out changes according to best practices and reliable data? This session includes a case study on change management at a large community college, as well as a discussion on the strategies and best practices used to help academic leaders implement the Guided Pathways Model.
Keywords: Change management; faculty; leadership; guided pathways; Community College